2011
DOI: 10.1007/jhep05(2011)052
|View full text |Cite
|
Sign up to set email alerts
|

Stable causality of Black Saturns

Abstract: We prove that the Black Saturns are stably causal on the closure of the domain of outer communications.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Studies of regularity and causal structure of black rings and Saturns can be found in[81,66,67,305,70] 6. It should be noted that, although formulated for 4-dimensional spacetimes, the results in[83] remain valid without changes in higher-dimensional spacetimes.…”
mentioning
confidence: 99%
“…Studies of regularity and causal structure of black rings and Saturns can be found in[81,66,67,305,70] 6. It should be noted that, although formulated for 4-dimensional spacetimes, the results in[83] remain valid without changes in higher-dimensional spacetimes.…”
mentioning
confidence: 99%
“…Therefore the only free parameter of model is a 1 . Using ansatz (32) in the corrected entropy (30) give us results which is illustrated by the Fig. 3.…”
Section: Corrected Thermodynamicsmentioning
confidence: 99%
“…It may be noted that conditions for meta-stability of a black Saturn have also been studied [31]. It has been demonstrated that the black Saturn is causal stably on the closure of the domain of outer communications [32]. The relation between the black Saturn and Myers-Perry black hole have also been analyzed [33].…”
Section: Introductionmentioning
confidence: 99%
“…A thorough analysis (see [1,10,11]) has shown that, under the assumption of parameters a i being pairwise distinct, the metrics in the Black Saturn family describe asymptotically flat, stably causal black hole space-times with smooth domains of outer communications. To guarantee the above listed desired properties of a well-behaved black hole space-time one needs to tune the parameters c 1 , c 2 , k and q in terms of a i 's.…”
Section: Introductionmentioning
confidence: 99%
“…To make the paper self-contained we present in the Appendix the Black Saturn metric of [1] in generalised Weyl coordinates. For the details of construction and properties we refer the reader to [1] and [10,11].…”
Section: Introductionmentioning
confidence: 99%